Why Vocational School Principals Must Be Different: A Strategic Leadership Perspective - Suhar Jendro (GHAITSA : Islamic Education Journal, 2025)
This study investigates the distinct leadership demands of vocational school principals through a systematic literature review (SLR), aiming to uncover strategic leadership practices that differentiate their role from principals in general education. With vocational education increasingly pivotal in aligning with industry needs and labor market dynamics, principals must adopt innovative, adaptive approaches to bridge the gap between education and employment. The methodology analyzes peer-reviewed articles, case studies, and reports (2010–2023), focusing on leadership styles, competencies, and strategies unique to vocational education. Findings reveal that vocational principals require industry-specific expertise, stakeholder collaboration, and flexible curriculum design to ensure institutional success. The study’s novelty lies in synthesizing strategic leadership frameworks tailored to vocational education’s unique challenges, offering fresh insights into effective leadership practices. Practical implications include recommendations for tailored leadership training programs and policy reforms to enhance vocational education outcomes. By emphasizing the critical role of vocational principals in preparing workforce-ready graduates and driving economic development, this research contributes to the broader discourse on educational leadership, highlighting their distinct responsibilities in shaping the future of vocational education